Cross-cultural adaptation and validation of Leicester Cough Questionnaire in sarcoidosis: the persian version - Rahdar, Mohammad; Kiani, Arda; Noorali, Sima; Bakhshandeh, Arezoo; Hosseini-Baharanchi, Fatemeh Sadat; Shafaghi, Shadi; Abedini, Atefeh; kharazmi, Amir Behnam (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Cough is a common symptom among patients with sarcoidosis, and the Leicester Cough Questionnaire, a cough-specific quality-of-life measure, evaluates the impact of cough across physical, psychological, and social domains in patients with chronic cough. The aim of this study was cross-cultural adaptation and validation of Persian version of Leicester Cough Questionnaire (LCQ) in pulmonary sarcoidosis in Iran. Methods: Psychometric analyses included translation and back translation of the questionnaire, face validity, content validity, construct validity, criterion-related validity, internal consistency, and test –retest reliability were performed. Results: Twenty-five participants demonstrated no major language barriers or difficulties in completing the questionnaire and adequate face validity of ≥1.5. Twelve experts confirmed the content validity was good (CVR˃0.56, I-CVI≤0.79, S-CVI/Ave˃0.80). Totally, 190 patients were included in the study. The Pearson’s coefficients and their significance’s (P<0.05) showed an acceptable agreement between the LCQ and the SF-36 questionnaire. The goodness-of-fit of the conceptual model including psychological, physical, and social domains, obtained from EFA, was confirmed throughout the RMSEA of 0.09 (<0.1), NFI of 0.9, NNFI of 0.91, and CFI of 0.92 which all were ≥0.9. The Persian LCQ showed an excellent internal consistency regarding Cronbach’s alpha of 0.974 and ICC (95%CI) value of 0.983 (0.977, 0.987). Conclusions: The psychometric properties showed that the Persian version of LCQ is a valid and reliable measure to evaluate cough-specific quality of life and is a fit-for-purpose measure for use in patients with pulmonary sarcoidosis and the results can guide clinicians in treatment decisions.